A KUALITAS PUTU AYU DENGAN SUBSTITUSI LABU KUNING: Substitusi Putu Ayu Labu Kuning - Syajida, Jihan; Holinesti, Rahmi; Faridah, Anni; Siregar, Juliana (Department of Food Technology, Universitas Pasundan, Bandung, 2025)
Putu ayu is a traditional Indonesian steamed cake made from a mixture of wheat flour, eggs, coconut milk, and grated coconut. This cake has a sweet and savory flavor with a soft texture; however, the use of wheat flour as the main ingredient result in relatively low fiber content and still relies on imported materials. This study aimed to analyze the effect of steamed pumpkin substitution on the quality of putu ayu in terms of square shape, neat shape, color, aroma, soft texture, expanded volume texture, and taste. The research was conducted in May 2025 at the Culinary Arts Workshop, Department of Family Welfare Science, Faculty of Tourism and Hospitality, Universitas Negeri Padang. This study employed a true experimental method using a Completely Randomized Design (CRD) with 4 treatments and 3 replications: 0% (X0), 10% (X1), 20% (X2), and 30% (X3) pumpkin substitution. Organoleptic testing was carried out involving 30 semi-trained panelist to assess the quality of putu ayu. The data were tabulated using ANOVA; if F-count > F-table, further analysis was conducted using Duncan”s Multiple Range Test. The results showed that pumpkin substitution had a significant effect on all quality parameters. Treatment X0 (0%) obtained the highest scores for square shape (3,74), neat shape (3,68), soft texture (3,39), and expanded volume texture (3,86), while treatment X3 (30%) showed the best results in term of color, aroma, and taste. Therefore, the best quality of steamed putu ayu was achieved with 30% steamed pumpkin substitution.